2022
DOI: 10.1088/1755-1315/1024/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Production of Clove Oil Nanoemulsion Using Whey Protein- Maltodextrin Conjugates and Chitosan

Abstract: Clove oil has benefits for both food and pharmaceutical purposes. However its use is limited due to several properties such as susceptibility to oxidation, poor water solubility, react with other components, and toxic at high concentration. The limitation of its usage can be overcome through emulsion technology. Therefore, this study aims to obtain clove oil nanoemulsion through preparation using whey protein-maltodextrin conjugates. These conjugates act as an emulsifier and a first layer, meanwhile chitosan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is concluded that nanoemulsion of Kencur essential oil with maltodextrin as coating material and tween 80 as a surfactant at this ratio tends to be effective in producing small particle sizes. In contrast to the ratios in other formulas which produce larger particle sizes, namely 110-120 nm [17], 147 nm [18] and 220 nm [19]. Another data we get is the PI value.…”
Section: Effect Of Essential Oil Levels On Particle Sizementioning
confidence: 57%
“…It is concluded that nanoemulsion of Kencur essential oil with maltodextrin as coating material and tween 80 as a surfactant at this ratio tends to be effective in producing small particle sizes. In contrast to the ratios in other formulas which produce larger particle sizes, namely 110-120 nm [17], 147 nm [18] and 220 nm [19]. Another data we get is the PI value.…”
Section: Effect Of Essential Oil Levels On Particle Sizementioning
confidence: 57%
“…Meanwhile, the addition of maltodextrin as a nonadsorbing polymer with Tg higher than that of sucrose at 162 °C may prevent the powder from becoming sticky during the drying process and better yield [ 47 , 48 ]. Nevertheless, the larger size of DE 10–13 maltodextrin which has a larger size of 1800 g/mol, has steric hindrance of thus unable to reach the phosphate group and give protection during the drying process [ [49] , [50] , [51] , [52] ]. In addition, several studies also reported less protection from maltodextrin applied in a concentration of 20% (b/v).…”
Section: Discussionmentioning
confidence: 99%